2006
DOI: 10.1523/jneurosci.0675-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+Influx through Mechanosensitive Channels Inhibits Neurite Outgrowth in Opposition to Other Influx Pathways and Release from Intracellular Stores

Abstract: Ca2ϩ signals are known to be important regulators of neurite outgrowth and steering. Here we show that inhibiting Ca 2ϩ influx through stretch-activated channels using various compounds, including a highly specific peptide isolated from Grammostola spatulata spider venom (GsMTx4), strongly accelerates the rate of neurite extension on diverse substrata and within the intact spinal cord. Consistent with the presence of stretch-activated channels, we show that Ca 2ϩ influx is triggered by hypotonic solutions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 53 publications
9
86
1
1
Order By: Relevance
“…Tojima et al [17] found that calcium entry involving CICR and IICR produced an attractive response, whereas Ca 2+ signals without store entry invoked a repulsive response [17]. Furthermore, the method of calcium entry also affects axon outgrowth and growth cone motility [40,41]. Calcium influx through mechanosensitive stretch-activated channels decreases axon motility [41].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Tojima et al [17] found that calcium entry involving CICR and IICR produced an attractive response, whereas Ca 2+ signals without store entry invoked a repulsive response [17]. Furthermore, the method of calcium entry also affects axon outgrowth and growth cone motility [40,41]. Calcium influx through mechanosensitive stretch-activated channels decreases axon motility [41].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the method of calcium entry also affects axon outgrowth and growth cone motility [40,41]. Calcium influx through mechanosensitive stretch-activated channels decreases axon motility [41]. By contrast, calcium influx through other avenues (TRPC channels and intracellular stores) supports and promotes axon outgrowth [41].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of these effects have been observed at concentrations in the 10-100 µM range, while at concentrations of 5 µM or lower it can be considered a good preliminary tool to block TRPC-mediated influx. The lack of better options can explain its continued use in many studies, in particular in the field of neurite growth and orientation [80,85,86]. Inorganic ions, such as La 3+ (and Gd 3+ ), can block most of these channels [87], but with complex dose-response relationships; therefore, these tools have to be employed with caution.…”
Section: A New Entry In Calcium Dependent Neuronal Migration: the Trpmentioning
confidence: 99%